(untitled) (El Taco en la Brea, 2023)
A selection of Latin American women’s narratives shows them to act as memory machines, and maps of a contemporaneity in which violence and family history are inseparable. Narrators’ trans‒territorial position redraw the lines between inside and outside, and track their ancestor’s steps. Volverse Palestina (Lina Meruane, Chile), La tierra comenzaba a arder (Cynthia Edul, Argentina), Mar Negro and Infieles (Ana Arzoumanian, Argentina): in each text we encounter a narrative of loss, mourning and melancholy, in an oriental world dominated by colonialism, authoritarianism and violence. The writers take a political y ethical position.